Diagnostic potential of various laboratory tests for irritable bowel syndrome (IBS): a systematic review - Mansoor, Misha; Shafiq, Muhammad Hamza; Imran, Mahnoor; Mushtaq, Fiza; Iftikhar, Sana; Shafiq, Fuad (Journal of the Pakistan Medical Association, 2024)
Objective: To identify possible tests along with their accuracies that may be used to diagnose irritable bowel syndrome. Method: The systematic review comprised literature search on Cochrane Library, PubMed, Science Direct and Elsevier databases for randomised controlled trials and cohort studies conducted from January 1, 2015, to December 31, 2022, using appropriate key words and Boolean operators. Focus was kept on studies that reported irritable bowel syndrome diagnosis as the primary outcome. The risk of bias was assessed using quality assessment, data abstraction, and synthesis version 2. Results: Of the 2,798 studies initially identified, 10(0.35%) were analysed in detail. Of them, 4(40%) used enzyme-linked immunosorbent assay kits to test for anti-cytolethal distending toxin B and anti-vinculin levels, 2(20%) used the kits for serum cytokine profiling and serum calprotectin levels, and 4(40%) used either magnetic resonance imaging scans, faecal metabolic profiling, intestinal biopsy analysis with immunostaining or polymerase chain reaction for differential transfer-ribonucleic acid-derived small ribonucleic acid. Out of the 4(40%) studies on anti-cytolethal distending toxin B and anti-vinculin levels, optical densities >1.56 and >1.60 recorded 100% specificity for irritable bowel syndrome with diarrhoea, but sensitivity was 22%. In contrast, rectal biopsies for cell densities of somatostatin and peptide YY showed high sensitivity and specificity for irritable bowel syndrome ranging 80-90%. Conclusion: Enzyme-linked immunosorbent assay testing for anti-cytolethal distending toxin B and anti-vinculin as well as rectal biopsies for cell densities could be potential diagnostic tests for irritable bowel syndrome. Key Words: Irritable bowel syndrome, Diagnosis, Laboratory, ELISA.